2010
DOI: 10.2108/zsj.27.222
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence and Evolutionary Relationship inFejervarya cancrivorafrom Indonesia and Other Asian Countries Inferred from Allozyme and MtDNA Sequence Analyses

Abstract: To elucidate genetic divergence and evolutionary relationship in Fejervarya cancrivora from Indonesia and other Asian countries, allozyme and molecular analyses were carried out using 131 frogs collected from 24 populations in Indonesia, Thailand, Bangladesh, Malaysia, and the Philippines. In the allozymic survey, seventeen enzymatic loci were examined for 92 frogs from eight representative localities. The results showed that F. cancrivora is subdivided into two main groups, the mangrove type and the large- pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 26 publications
3
48
1
Order By: Relevance
“…There are still no studies on the effects of frog harvesting on natural populations. Our results show that the genetic and morphological diversity of the frogs in trade is much higher than the genetic and morphological diversity measured so far by scientific studies (Kurniawan et al 2010(Kurniawan et al , 2011. These results underline the need for large-scale studies on the taxonomy, population structure, reproductive data and ecology of the species concerned in international trade.…”
Section: Sustainability and Conservationcontrasting
confidence: 64%
See 1 more Smart Citation
“…There are still no studies on the effects of frog harvesting on natural populations. Our results show that the genetic and morphological diversity of the frogs in trade is much higher than the genetic and morphological diversity measured so far by scientific studies (Kurniawan et al 2010(Kurniawan et al , 2011. These results underline the need for large-scale studies on the taxonomy, population structure, reproductive data and ecology of the species concerned in international trade.…”
Section: Sustainability and Conservationcontrasting
confidence: 64%
“…The specimens studied in the present work may well come from newly harvested populations. In fact, the presence of F. moodiei in our samples, a species which has a known range outside Java and Sumatra, a range that includes the Philippines, the northern coasts of the Gulf of Thailand, Bangladesh and Orissa (Kurniawan et al 2010), indicates that the specimens studied here may have come from other islands than Java and south-eastern Sumatra.…”
Section: Sustainability and Conservationmentioning
confidence: 73%
“…Inger (1999) proposed that potentially unknown amphibian biodiversity needs to be explored by additional sampling in South Asia as it might disclose detailed information at the species level. In fact, many undescribed and/or cryptic species have been found in complexes previously thought to be single species in South to East Asian countries through morphological, allozyme, and molecular analyses, as well as crossing experiments (Hoplobatrachus and Euphlyctis: Alam et al, 2008;Hasan et al, 2012b;Fejervarya: Sumida et al, 2007;Islam et al, 2008aIslam et al, , 2008bKotaki et al, 2010;Kurniawan et al, 2010). In recent years, particularly on the Indian subcontinent, eyecatching discoveries of new species, genera, and/or families have been made (Biju and Bossuyt, 2003;Biju et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This reclassification resulted in the renaming of Rana cancrivora (Gravenhorst 1829; Annandale, 1918;Boulenger, 1920;Dunn, 1928) to Fejervarya cancrivora (Iskandar, 1998;Dubois and Ohler, 2000). Molecular and allozyme analyses by Kurniawan et al (2010) have revealed that Asian populations of F. cancrivora can be divided into three types, namely, the mangrove-, large-, and Pelabuhan Ratu/Sulawesi-types, with the latter two types showing the most similarity. Data from the same study indicate that the mangrove-type is distributed in the Asian mainland and the Philippines, the large-type in Sundaland, and the Pelabuhan Ratu/Sulawesi-type in Pelabuhan Ratu, Java Island and Sulawesi Island of Indonesia.…”
Section: Introductionmentioning
confidence: 99%